2013
DOI: 10.1371/journal.pone.0075899
|View full text |Cite
|
Sign up to set email alerts
|

Can Proliferation Biomarkers Reliably Predict Recurrence in World Health Organization 2003 Defined Endometrial Stromal Sarcoma, Low Grade?

Abstract: An estimated 1500–3000 invasive Endometrial Stromal Sarcomas (ESS) cases annually occur worldwide. Before 2003, ESS was divided as low and high grade ESS based on mitotic activity. In 2003 the WHO changed the names, excluded mitoses and made nuclear atypia and necrosis the essential diagnostic criteria to distinguish ESS, Low Grade (ESS-LG, recurrence-free survival >90%) and Undifferentiated Endometrial Sarcoma (UES, poor prognosis). We have evaluated in WHO2003 defined ESS-LG whether proliferation biomarkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…6 High-grade ESS is now defined as a tumor composed of atypical cells resembling endometrial stromal cells but lacking the degree of atypia and pleomorphism of UUS (Figure 8). 44,45 The separate identity of this high-grade ESS was further confirmed by a specific YWHAE-FAM22 gene rearrangement. 46 Undifferentiated uterine sarcomas are now defined as high-grade sarcomas lacking evidence of endometrial stromal morphology combined with severe cytologic atypia, often with multinucleated and bizarre cells and brisk mitotic activity (.20 mitoses/10 HPFs).…”
Section: Historical Perspective and Evolving Conceptsmentioning
confidence: 69%
“…6 High-grade ESS is now defined as a tumor composed of atypical cells resembling endometrial stromal cells but lacking the degree of atypia and pleomorphism of UUS (Figure 8). 44,45 The separate identity of this high-grade ESS was further confirmed by a specific YWHAE-FAM22 gene rearrangement. 46 Undifferentiated uterine sarcomas are now defined as high-grade sarcomas lacking evidence of endometrial stromal morphology combined with severe cytologic atypia, often with multinucleated and bizarre cells and brisk mitotic activity (.20 mitoses/10 HPFs).…”
Section: Historical Perspective and Evolving Conceptsmentioning
confidence: 69%
“…The most frequent chromosomal rearrangement is the t(7;17), which results in the production of a JAZF1‐JJAZ1 fusion RNA transcript. Other genes that have been involved in fusion transcripts include the PHD finger protein 1 (PHF1) and enhancer of polycomb 1 (EPC1) …”
mentioning
confidence: 99%
“…Overall, SFRP4 seems to act as a tumor suppressor gene regulating the cytosolic ß-catenin pool in the cell. Interestingly, Feng et al found that proliferation markers, such as Ki-67, are also predictive for a high recurrence of ESS [40]. By using immunostaining, Ng et al detected nuclear ß-catenin staining in 40% of ESS and suggested this method to be potentially useful for diagnosis, especially for distinguishing ESS from leiomyosarcoma, which are negative for nuclear ß-catenin [41].…”
Section: Wnt Pathway Deregulation In Ess/uesmentioning
confidence: 99%